Pengaruh Literasi Keuangan Dan Pendapatan Mahasiswa Akuntansi Terhadap Keputusan Investasi Dengan Pengendalian Diri Sebagai Variabel Moderasi - Megawati Megawati; Fidya Wati J. Lagaramusu; Tiara Nur Fatanah; Andi Mattulada Amir; Erwinsyah Erwinsyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The surge in digital investment platforms has boosted student participation in financial markets, yet gaps persist in understanding behavioral moderators among accounting students. This study examines the influence of financial literacy and income on investment decisions, with self-control as a moderating variable, among accounting students at Universitas Tadulako. Employing a quantitative explanatory approach, data were collected via online Likert-scale questionnaires from 104 respondents, yielding 93 valid samples through purposive sampling. Analysis utilized Moderated Regression Analysis (MRA) in SPSS 27, including validity-reliability tests, classical assumptions, t-test, F-test, and R-squared. Findings reveal financial literacy significantly affects investment decisions (sig. 0.018 < 0.05, β=0.087), while income, self-control, and moderation effects do not (sig. >0.05), with the model explaining only 4.2% variance. In conclusion, financial knowledge dominates, recommending curriculum enhancements for behavioral training despite model limitations.